Dynamic contrast-enhanced ultrasound for assessment of therapy effects on skeletal muscle microcirculation in peripheral arterial disease: pilot study - Amarteifio, Erick; Wormsbecher, Stephanie; Demirel, Serdar; Kauczor, Hans-Ulrich; Böckler, Dittmar; Weber, Marc-André (European journal of radiology, 2013)
OBJECTIVE: To assess with dynamic contrast-enhanced ultrasound (CEUS) and transient arterial occlusion whether the muscular micro-perfusion in patients with peripheral arterial disease (PAD) is improved after angioplasty or surgery. MATERIALS AND METHODS: This study had local institutional review board approval. Written informed consent was obtained from all 20 patients with PAD, Fontaine stage IIb (mean age, 64 years), who participated in the study. Low-MI CEUS (7MHz; MI, 0.28) was applied to the mainly affected lower leg after start of a continuous automatic intravenous injection of 4.8mL SonoVue(®). Muscle-perfusion was monitored by CEUS before, during, and after provocation by arterial occlusion at the thigh level lasting for 60s. CEUS examination was performed a second time within 14 days after angioplasty (n=15), thrombendarterectomy (n=2), angioplasty and thrombendarterectomy (n=1), or bypass (n=2). Clinical amelioration was re-evaluated within 6 months after the intervention using a 4-point scale. RESULTS: Ankle-brachial-index (ABI) increased from 0.8±0.2 to 0.9±0.3 after treatment (p=0.01). Time to maximum CEUS signal (tmax) shortened from 26±14s to 14±4s (p=0.004). The slope to maximum after transient occlusion (m2) changed to steeper values (6.4±5.8∼mL/s versus 10.2±5.0∼mL/s; p=0.04). Shortened tmax predicted improvement in the patients' intermittent leg pain and therefore successful therapy outcome. CONCLUSION: Dynamic CEUS with transient arterial occlusion can visualize the treatment-induced improvement of muscular micro-perfusion in patients with PAD.